Clinical significance of the LacdiNAc‐glycosylated prostate‐specific antigen assay for prostate cancer detection. Issue 8 (27th June 2019) - Yoneyama, Tohru; Tobisawa, Yuki; Kaneko, Tomonori; Kaya, Takatoshi; Hatakeyama, Shingo; Mori, Kazuyuki; Sutoh Yoneyama, Mihoko; Okubo, Teppei; Mitsuzuka, Koji; Duivenvoorden, Wilhelmina; Pinthus, Jehonathan H.; Hashimoto, Yasuhiro; et al.
Abstract: To reduce unnecessary prostate biopsies (Pbx), better discrimination is needed. To identify clinically significant prostate cancer (CSPC) we determined the performance of LacdiNAc‐glycosylated prostate‐specific antigen (LDN‐PSA) and LDN‐PSA normalized by prostate volume (LDN‐PSAD). We retrospectively measured LDN‐PSA, total PSA (tPSA), and free PSA/tPSA (F/T PSA) values in 718 men who underwent a Pbx in 3 academic urology clinics in Japan and Canada (Pbx cohort) and in 174 PC patients who subsequently underwent radical prostatectomy in Australia (preop‐PSA cohort). The assays were evaluated using the area under the receiver operating characteristics curve (AUC) and decision curve analyses to discriminate CSPC. In the Pbx cohort, LDN‐PSAD (AUC 0.860) provided significantly better clinical performance for discriminating CSPC compared with LDN‐PSA (AUC 0.827, P  = 0.0024), PSAD (AUC 0.809, P  < 0.0001), tPSA (AUC 0.712, P  < 0.0001), and F/T PSA (AUC 0.661, P  < 0.0001). The decision curve analysis showed that using a risk threshold of 20% and adding LDN‐PSA and LDN‐PSAD to the base model (age, digital rectal examination status, tPSA, and F/T PSA) permitted avoidance of even more biopsies without missing CSPC (9.89% and 18.11%, respectively vs 2.23% [base model]). In the preop‐PSA cohort, LDN‐PSA values positively correlated with tumor volume and tPSA and were significantly higher in pT3, pathological Gleason score ≥ 7. Limitations include limited sample size, retrospective nature, and no family history information prior to biopsy. LacdiNAc‐glycosylated PSA is significantly better than the conventional PSA test in identifying patients with CSPC. This study was approved by the ethics committee of each institution ("The Study about Carbohydrate Structure Change in Urological Disease"; approval no. 2014‐195). Abstract : We evaluated the clinical significance of LacdiNAc‐glycosylated prostate‐specific antigen (LDN‐PSA) and LDN‐PSA normalized by prostate volume (LDN‐PSAD). We retrospectively measured LDN‐PSA, PSA, and free PSA/total PSA (F/T) PSA values using 718 men who had prostate biopsy in 3 academic urology sites (Japan and Canada) and 174 prostate cancer patients who underwent radical prostatectomy in Australia. It was observed that inclusion of LDN‐PSA and LDN‐PSAD to the base diagnostic model (age, digital rectal examination status, tPSA, and F/T PSA) permitted avoidance of even more biopsies without missing clinically significant prostate cancer, indicating that LDN‐PSA and LDN‐PSAD are significantly better than the conventional PSA test in identifying patients with clinically significant prostate cancer.